E-Service Quality and Customer Satisfaction: With Reference to Atm Services of State Banks in Sri Lanka - M. S. Ishar Ali; J. Resi Tony; V. Anputhasan (Research Parks Publishers, 2022)
The purpose of this article is to investigate the quality of e-services and customer satisfaction in relation to ATM banking services, using theoretical foundations as a basis for investigation. The relationship between e-service quality and customer perception has received less attention from researchers, despite the fact that researchers have become increasingly interested in e-services' quality dimensions. There is a clear need for research into both the quality dimensions of e-services and the customer satisfaction dimensions that are relevant in the service context. In this article, quantitative analysis and data from respondents were used in conjunction with a convenient sampling technique. The study discovered that reliability, responsiveness, efficiency, privacy, empathy, and efficiency are all significant factors influencing customer satisfaction when using ATM banking services. As a result, the study concluded that reliability, responsiveness, efficiency, privacy, empathy, and efficiency are all significant factors influencing customer satisfaction when using ATM banking services.